Overview of microgrid systems - V. Saravanan; K. M. Venkatachalam; M. Arumugam; M. A. K. Borelessa; K. T. M. U. Hemapala (International Journal of Advances in Applied Sciences, 2021)
This research paper discusses the different types of microgrids, their structural arrangements and the technology adopted for different power management projects. It also deals with various control strategies and security plans used for optimal performance. A detailed overview of the direct current (DC) microgrid system is discussed, outlining its configurations and technical-economic aspects. Performance evaluation of microgrid carried out through various reliability codes is also provided.